2018
DOI: 10.1155/2018/6742384
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Type 2 Diabetes Mellitus Occurrence Using Three-Dimensional Anthropometric Body Surface Scanning Measurements: A Prospective Cohort Study

Abstract: Background An accurate and comprehensive anthropometric measure for predicting type 2 diabetes mellitus (T2DM) has not yet been depicted. Methods A total of 8450 nondiabetic participants were recruited during 2000–2010 in Taiwan. The cohort was followed up to the end of 2013, over an average of 8.87 years. At recruitment, participants completed a questionnaire related to basic demographics, lifestyle variables, personal disease history, and family disease history. 3D body surface scanning was used to obtain 35… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 41 publications
1
20
0
Order By: Relevance
“…However, in this study, we observed that smaller measurements of the lower limbs increased the risk of diseases, whereas the smaller measurements of the upper limbs and visceral fat accumulation synergistically increased the risk of diseases. Although studies have indicated that thigh circumference is negatively associated with T2DM, dementia, and cancer 12 , 16 , 17 , this study confirmed that it is a long-term predictor of sarcopenia-associated chronic diseases. The present study proposes using the ABMS, which involves the use of upper arm, waist, and thigh measurements for its calculation, as a reliable biomarker for predicting sarcopenia-associated chronic diseases.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…However, in this study, we observed that smaller measurements of the lower limbs increased the risk of diseases, whereas the smaller measurements of the upper limbs and visceral fat accumulation synergistically increased the risk of diseases. Although studies have indicated that thigh circumference is negatively associated with T2DM, dementia, and cancer 12 , 16 , 17 , this study confirmed that it is a long-term predictor of sarcopenia-associated chronic diseases. The present study proposes using the ABMS, which involves the use of upper arm, waist, and thigh measurements for its calculation, as a reliable biomarker for predicting sarcopenia-associated chronic diseases.…”
Section: Discussionsupporting
confidence: 58%
“…The lower limbs account for approximately 70% of muscle mass. Studies have indicated that larger hip and thigh circumferences are associated with a low risk of T2DM, dementia, and internal cancers, independent of sociodemographic variables 12 , 16 , 17 . The soft tissue in the thigh is mostly composed of muscle mass and subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The disease prevalence is likely to increase in the coming years considering that it is the fastest-growing chronic disease in the world. [ 5 ] However, our findings suggest that about 330 to 660 million USD (10–20 billion NTD) could be saved annually if Taiwanese adults with DM could adopt a more active lifestyle.…”
Section: Discussionmentioning
confidence: 86%